Pendidikan Kristiani Berbasis Multikultural dalam Konteks Moderasi Beragama di SMP Negeri 2 Arso - Satria Mahardhika; Nining Puji Lestari; Olivia Cherly Wuwung (Jurnal Ilmiah Wahana Pendidikan, 2022)
Pluralism is the culture of the Indonesian nation as well as an asset of national identity. In a multicultural nation, horizontal conflicts often occur. Multicultural education plays an important role in Indonesian society because of the country’s reputation for embracing diversity and resolving conflicts that may develop as a result of societal change and reform in a way that contributes to the betterment of the entire nation. In the junior high school 2 Arso has diverse ethnicities and cultures, and This can lead to different opinions. Christian students dominate. Every social institution that occurs is legally influenced by who dominates. This article aims to build school life in the context of religious moderation through multicultural-based Christian education. The method used is descriptive qualitative research method and tends to use analysis. Process and meaning (subject perspective) are more highlighted in qualitative research. The importance of building Christian education based on cultural diversity as a reflection of Indonesians in religion in a pluralistic public space. In conclusion, Christian education can be a way to build a moderate and inclusive social life for students